Scanning optical microscopy of semiconductor devices - McCabe, E; McCabe, Eithne (1987)
This thesis explores the interaction of light and semiconductors using a scanning optical microscope. A key advantage to this approach is its non-destructiveness. This is a critical factor in the assurance of semiconductor device reliability. This research investigates novel ways in which the light beam of a scanning optical microscope may be used to detect defects in semiconductors. Attention is focused on the use of the optical beam induced current technique (OBIC). This method permits the imaging of defects in semiconductor devices which may affect the electrical performance of these devices. For the first time a theory has been developed which forms the basis of an understanding of how excess minority carriers are distributed in a semiconductor when probed with a with a finely focused light beam. This theory is used to predict the resolution of device defects imaged using OBIC. This work is particularly important in that it may incorporate the exact light probe distribution in the semiconductor material which is calculated in this thesis. A new method to display low contrast OBIC images has been used to highlight defects in semiconductor devices. In addition an exciting novel method to obtain spatial information on the distribution of defects at the silicon/silicon-dioxide interface in metal oxide semiconductor devices has been found. This method can examine many defects which cause serious problems for device manufacturers including the effect of radiation damage on device performance. Other non-destructive techniques which can complement OBIC imaging are explored including photoluminescence and infrared transmission imaging. Additional research is proposed for the future. This research in conjunction with the research in this thesis would allow a comprehensive and powerful examination approach of both static and dynamic conditions of semiconductor devices.